Lymph Node Assessment in Endometrial Cancer: Towards Personalized Medicine - Fabien Vidal; Arash Rafii (Hindawi Limited, 2013)
Endometrial cancer (EC) is the most common malignancy of the female reproductive tract and is increasing in incidence. Lymphovascular invasion and lymph node (LN) status are strong predictive factors of recurrence. Therefore, the determination of the nodal status of patients is mandatory to optimally tailor adjuvant therapies and reduce local and distant recurrences. Imaging modalities do not yet allow accurate lymph node staging; thus pelvic and aortic lymphadenectomies remain standard staging procedures. The clinical data accumulated recently allow us to define low- and high-risk patients based on pre- or peroperative findings that will allow the clinician to stratify the patients for their need of lymphadenectomies. More recently, several groups have been introducing sentinel node mapping with promising results as an alternative to complete lymphadenectomy. Finally, the use of peroperative algorithm for risk determination could improve patient's staging with a reduction of lymphadenectomy-related morbidity.